The Value of Character Education in a Collection of Fairy Tales by Ungu Lianza - Mutiara, Helmi; Yatri, Ika (MIMBAR PGSD Undiksha, 2022)
Fairy tales have moral values ​​that can be used as an alternative to character learning in children. Fairy tales can provide information related to the value of character education. This study aims to analyze the value of character education in the collection of fairy tales by Ungu Lianza in grade 2 elementary school. This research is a qualitative method using the literature description of the library—methods of data collection using interviews and documentation. Qualitative research in this study was conducted by collecting data by observing the situation that occurred following the circumstances without being manipulated or influenced. The data analysis technique used qualitative analysis a collection of fairy tales by Ungu Lianza and the implications of character values ​​in everyday life. Grade 2 students in everyday life apply character values, increase interest in reading story books through the Ungu Lianza fairy tale book, and understand the values ​​of other characters. Teachers can also put in the personality values ​​of students to have the traits of tolerance, cooperation, independence, discipline, responsibility, and integrity. This research implies that teachers in the learning process can apply character education through fairy tales to students. So it can be applied in everyday life.